1
$\begingroup$

I want to find the solution of $$ \frac{\partial u}{\partial y} = \frac{\partial^2 u}{\partial x^2}$$ I know I can solve it if there were some initial conditions but I want to find the general solution for it, I tried a linear change of variable but it didn't work.

$\endgroup$
  • 5
    $\begingroup$ This is heat equation. $\endgroup$ – user658409 Aug 31 '19 at 13:46
  • $\begingroup$ Hint: Fundamental solution $\endgroup$ – I was suspended for talking Aug 31 '19 at 13:49
0
$\begingroup$

Similar to PDE - solution with power series:

Let $u(x,y)=\sum\limits_{n=0}^\infty\dfrac{(x-a)^n}{n!}\dfrac{\partial^nu(a,y)}{\partial x^n}$ ,

Then $u(x,y)=\sum\limits_{n=0}^\infty\dfrac{(x-a)^{2n}}{(2n)!}\dfrac{\partial^{2n}u(a,y)}{\partial x^{2n}}+\sum\limits_{n=0}^\infty\dfrac{(x-a)^{2n+1}}{(2n+1)!}\dfrac{\partial^{2n+1}u(a,y)}{\partial x^{2n+1}}=\sum\limits_{n=0}^\infty\dfrac{(x-a)^{2n}}{(2n)!}\dfrac{\partial^nu(a,y)}{\partial y^n}+\sum\limits_{n=0}^\infty\dfrac{(x-a)^{2n+1}}{(2n+1)!}\dfrac{\partial^{n+1}(a,y)}{\partial y^n\partial x}=\sum\limits_{n=0}^\infty\dfrac{f^{(n)}(y)(x-a)^{2n}}{(2n)!}+\sum\limits_{n=0}^\infty\dfrac{g^{(n)}(y)(x-a)^{2n+1}}{(2n+1)!}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.